1967
DOI: 10.1172/jci105510
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Suppression of Proximal Tubular Reabsorption by Saline Infusions*

Abstract: Summary. The mechanism by which expansion of extracellular fluid volume with isotonic saline suppresses reabsorption in the proximal tubule was studied in rats by examining the relations among glomerular filtration rate (GFR), absolute and fractional reabsorption of filtrate, intrinsic reabsorptive capacity (rate of reabsorption per unit tubular volume), transit time, and tubular volume.Saline infusions reduced the per cent of the glomerular filtrate reabsorbed in the proximal tubule from 50% during antidiures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
1
3

Year Published

1968
1968
1980
1980

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 21 publications
11
52
1
3
Order By: Relevance
“…Rector, Sellman, Martinez-Maldonado, and Seldin observed a 40% inhibition of the intrinsic reabsorptive capacity of the proximal convoluted tubule in the rat after furosemide, as measured by the shrinking drop technique (7). Nevertheless, in agreement with the results in the dog (8) and monkey (6), they were unable to detect an inhibitory effect of the drug in the rat on fractional sodium reabsorption by the proximal tubule as measured in free flow studies.…”
Section: Introductionmentioning
confidence: 74%
“…Rector, Sellman, Martinez-Maldonado, and Seldin observed a 40% inhibition of the intrinsic reabsorptive capacity of the proximal convoluted tubule in the rat after furosemide, as measured by the shrinking drop technique (7). Nevertheless, in agreement with the results in the dog (8) and monkey (6), they were unable to detect an inhibitory effect of the drug in the rat on fractional sodium reabsorption by the proximal tubule as measured in free flow studies.…”
Section: Introductionmentioning
confidence: 74%
“…Watson (1966) concluded that all the increased sodium excreted could be accounted for by the decreased fractional reabsorption of sodium in the proximal tubule. The mechanism of this increased proximal tubular rejection of sodium as a result of saline loading is unknown (Rector, Sellman, Martinez-Maldonado & Seldin, 1967). The above evidence gives some basis for the validity of our use of the changes in tubular rejection fractions to explain the renal tubular effect of these drugs.…”
Section: Relative Importance Of Tubular Rejection and Filtered Loadsmentioning
confidence: 88%
“…To the extent however, that the punctured segments identified by lissamine green do not represent a fixed anatomical portion of the entire proximal convolution, it is possible that small, but significant differences in fractional reabsorption of salt and water could be obscured by an unrecognized random pattern to the tubular punctures. Although no comparable data exist for the dog, Rector, Sellman, Martinez-Maldonado, and Seldin (20) have shown by micropuncture and microdissection techniques that the end-proximal tubule in rats as identified by lissamine green injections corresponds to 55-65% of the total length of the proximal tubule. If this were also the situation in dogs, then conclusions concerning fractional reabsorption in both groups of dogs are probably valid.…”
Section: Methodsmentioning
confidence: 97%